Gene activation-associated long noncoding RNAs function in mouse preimplantation development - Hamazaki, Nobuhiko (Development, 2015)
In mice, zygotic activation occurs for a wide variety of genes, mainly at the 2-cell stage. Long noncoding RNAs (lncRNAs) are increasingly being recognized as modulators of gene expression. In this study, directional RNA-seq of MII oocytes and 2-cell embryos identified more than 1000 divergently transcribed lncRNA/mRNA gene pairs. Expression of these bidirectional promoter-associated noncoding RNAs (pancRNAs) was strongly associated with the upregulation of their cognate genes. Conversely, knockdown of three abundant pancRNAs led to reduced mRNA expression, accompanied by sustained DNA methylation even in the presence of enzymes responsible for DNA demethylation. In particular, microinjection of siRNA against the abundant pancRNA partner of interleukin 17d (Il17d) mRNA at the 1-cell stage caused embryonic lethality, which was rescued by supplying IL17D protein in vitro at the 4-cell stage. Thus, this novel class of lncRNAs can modulate the transcription machinery in cis to activate zygotic genes and is important for preimplantation development.